2005
DOI: 10.1074/jbc.m500308200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Prothoracicostatic Hormone and Its Receptor in the Silkworm Bombyx mori

Abstract: The insect brain regulates the activity of the prothoracic glands to secrete ecdysteroids, which affect growth, molting, and metamorphosis. Here we report the identification of a novel prothoracicostatic factor and its receptor in the silkworm Bombyx mori. The prothoracicostatic factor purified from pupal brains of B. mori is a decapeptide with the conserved structure of an insect myosuppressin and thus named Bommo-myosuppressin. Bommo-myosuppressin dose dependently suppressed the cAMP level and inhibited ecdy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 39 publications
5
84
1
1
Order By: Relevance
“…To elucidate the prothoracicostatic activity of BRFa, cAMP and ecdysteroid assays were performed by using PGs of the fifth larval instar on day 4, as described for BMS in ref. 12. As shown in Fig.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…To elucidate the prothoracicostatic activity of BRFa, cAMP and ecdysteroid assays were performed by using PGs of the fifth larval instar on day 4, as described for BMS in ref. 12. As shown in Fig.…”
Section: Resultsmentioning
confidence: 82%
“…We developed an ELISA system to purify endogenous FaRPs in Bombyx, in addition to BMS. Competitive ELISA revealed that some HPLC fractions, originally prepared from Bombyx pupal brains for the purification of BMS (12), show FMRFamide-like immunoreactivity (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prehybridization solution was prepared as reported previously [58]. After 2 h of prehybridization at 50 °C, DIG-labelled RNA probe, produced by in vitro transcription system (Promega) and DIG RNA Mix (Roche), were added into the same buffer.…”
Section: Whole-mount In Situ Hybridizationmentioning
confidence: 99%